Issues and challenges of radicalism in Pondok Institutions in Malaysia - Ishak, Mohd Haizi; Ismail, Halim (Yayasan Dakwah Islamiah Malaysia (YADIM), 2022)
Pondok institution is the oldest Islamic religious institution in the area of Nusantara that still exists and flourishes to this date. After the tragedy of September 11, there are challenges faced by this institution, especially in the matter of radical ideology. This study was conducted to analyze the radical thinking among Pondok institutions and to identify responses to challenges faced by their institutions after the tragedy of September 11. This research applies a qualitative method, where the approach of content analysis is emphasized. The findings show that radicalism in Pondok institutions is usually radicalized through unstructured ideology through the internet and social media and not through the guarded pedagogy of the Pondok institutions. The pedagogy of teaching and learning in Pondok is recommended to be improved and strengthened so that the institution will forever be flourished despite the challenges of radicalism and political condition.